The Service Learning to Cultivate Soft Skills for the Management of Darul Qur'an - Athok Fuadi; Idam Mustofa; Yoke Suryadarma; Saiful Anwar; Defi Firmansah (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2023)
Developing the potential of educational institution administrators with a focus on improving the quality of learning and administrative management is essential in nurturing the Holy Qur’an School. This community service aims to guide the administrators of Darul Qur'an Holy Qur’an School to empower their soft skills to enhance the quality of education and management. This mentoring employs the service learning method, strongly emphasizing developing soft skills, particularly focusing on empathetic abilities and emotional regulation in unlocking potential. The outcomes of this service learning initiative include enriching student worship practices, enhancing the capacity of educators through mentoring in recitation methods, and supporting operational permit management. From these results, it has been observed that administrators were able to develop soft skills, including social awareness, problem-solving, communication, self-discovery, and leadership skills.